2005
DOI: 10.1534/genetics.104.039750
|View full text |Cite
|
Sign up to set email alerts
|

A Screen for Genes That Influence Fibroblast Growth Factor Signal Transduction in Drosophila

Abstract: The misexpression of an activated form of the FGF receptor (FGFR) Breathless in conjunction with downstream-of-FGF-receptor (Dof), an essential signaling molecule of the FGF pathway, in the Drosophila eye imaginal discs impairs eye development and results in a rough eye phenotype. We used this phenotype in a gain-of-function screen to search for modifiers of FGF signaling. We identified 50 EP stocks with insertions defining at least 35 genes that affect the rough eye phenotype. Among these genes, 4 appear to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 35 publications
(4 reference statements)
0
28
0
Order By: Relevance
“…Several studies have shown that misexpression of MESR4 can modify the signaling pathway activated by fibroblast growth factor, PDGF/VEGF-like growth factor, Rac, or Cdc42 (Raymond et al, 2004;Zhu et al, 2005). Overexpression of MESR4 alone causes various defects in the adult fly morphology, such as loss of macrocheatae and dorsal thorax cleft (Abdelilah-Seyfried et al, 2000;Pena-Rangel et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that misexpression of MESR4 can modify the signaling pathway activated by fibroblast growth factor, PDGF/VEGF-like growth factor, Rac, or Cdc42 (Raymond et al, 2004;Zhu et al, 2005). Overexpression of MESR4 alone causes various defects in the adult fly morphology, such as loss of macrocheatae and dorsal thorax cleft (Abdelilah-Seyfried et al, 2000;Pena-Rangel et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…For example, a genetic screen for modifiers of RTK signaling in the Drosophila eye uncovered a number of genes specific to FGF receptor signaling, or common to both FGF receptor and PVR signaling but not to EGF receptor activation (Zhu et al 2005). During Drosophila oogenesis, EGFR and PVR appear to have overlapping but not identical functions in follicle cell migration (Duchek et al 2001), while cell proliferation and survival in the developing Drosophila larval dorsal thoracic air sac requires the EGF receptor but not FGF receptor signaling (Cabernard and Affolter 2005).…”
Section: Resultsmentioning
confidence: 99%
“…S3 in the supplementary material). By contrast, halving the dose of fas2 suppressed the phenotype caused by misexpression in the eye of an activated form of the FGF receptor Breathless in conjunction with Downstream-of-FGF-receptor (Dof) (Zhu et al, 2005) (see Fig. S3 in the supplementary material).…”
Section: Specificity Of Interaction Between Egfr and Fas2mentioning
confidence: 99%